Comparison Income Group Farmers Members Alam BendunganAnd Non A Member Of The Farmers In The Village Sungai Paku Kampar Left Sub-District District Kampar The Province Of Riau - Ivo Alidra Ys; Firman Nugroho; Kusai ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted in August 2015 located in the village Sungai Paku Subsdistrict Kampar Kiri District Kampar the Province Riau. Research aims to: 1) explain the differences in the means of production (input supply) of owned members of the group farming and non the farmers to cultivator of the; 2) explained the difference in the number and value of production owned members of the group farming and non the farmers; and 3) explain the differences in the cost and income owned members of the group farming and non the farmers to cultivator.Methods used in research it will be a method of survey to the determination of the respondents in proportional sampling.Based on research results obtained, it can be argued that there is no difference the use of production facilities (seeds and feed) owned by cultivator of the that in groups with cultivator of the non groups at a venture the cultivation of fish system buoyant cages net village in the Sungai Paku subsdistrict Kampar Kiri district Kampar. Then, there is a difference production average and the resulting cultivator of the production, where cultivator of the in groups produce production more than cultivator of the non groups farming.This is causing differences in net income average produced cultivator of the, a cultivator of the in groups produce income more than cultivator of the non groups farming.Keywords: comparison, input supply, income